Functional characterization of four opsins and two G alpha subtypes co-expressed in the molluscan rhabdomeric photoreceptor - Ryota Matsuo; Mitsumasa Koyanagi; Tomohiro Sugihara; Taishi Shirata; Takashi Nagata; Keiichi Inoue; Yuko Matsuo; Akihisa Terakita (BMC Biology, 2023)
Abstract Background Rhabdomeric photoreceptors of eyes in the terrestrial slug Limax are the typical invertebrate-type but unique in that three visual opsins (Gq-coupled rhodopsin, xenopsin, Opn5A) and one retinochrome, all belonging to different groups, are co-expressed. However, molecular properties including spectral sensitivity and G protein selectivity of any of them are not determined, which prevents us from understanding an advantage of multiplicity of opsin properties in a single rhabdomeric photoreceptor. To gain insight into the functional role of the co-expression of multiple opsin species in a photoreceptor, we investigated the molecular properties of the visual opsins in the present study. Results First, we found that the fourth member of visual opsins, Opn5B, is also co-expressed in the rhabdomere of the photoreceptor together with previously identified three opsins. The photoreceptors were also demonstrated to express Gq and Go alpha subunits. We then determined the spectral sensitivity of the four visual opsins using biochemical and spectroscopic methods. Gq-coupled rhodopsin and xenopsin exhibit maximum sensitivity at ~ 456 and 475 nm, respectively, and Opn5A and Opn5B exhibit maximum sensitivity at ~ 500 and 470 nm, respectively, with significant UV sensitivity. Notably, in vitro experiments revealed that Go alpha was activated by all four visual opsins, in contrast to the specific activation of Gq alpha by Gq-coupled rhodopsin, suggesting that the eye photoreceptor of Limax uses complex G protein signaling pathways. Conclusions The eye photoreceptor in Limax expresses as many as four different visual opsin species belonging to three distinct classes. The combination of opsins with different spectral sensitivities and G protein selectivities may underlie physiological properties of the ocular photoreception, such as a shift in spectral sensitivity between dark- and light-adapted states. This may be allowed by adjustment of the relative contribution of the four opsins without neural networks, enabling a simple strategy for fine-tuning of vision.